Infrastructure Growth, External Debt and Exchange Rate Nexus in Africa - Akplehey, F.N. (University of Ghana, 2019)
The econometric nexus among infrastructure growth, external debt and Exchange Rate in the Sub-Sahara Africa region has been investigated. The study period covered 1980 to the year 2017 for 42 countries in the Sub-Sahara Africa region. The study utilized co-integration and Vector Error Correction Mechanism, a type of Panel Vector Autoregression to test the nexus between infrastructure growth, external debt, and real exchange. Granger causality test examines the causal nexus among the variables. The unit root tests showed all variables to be integrated after taking the first difference. The Johansen cointegration result shows the variables to be co-integrated. The results show a short-run and long-run association among the variables. Moreover, the finding suggests bidirectional Granger causality between infrastructure growth and external debt, a unidirectional Granger causality that runs from Exchange Rate to external debt, and a unidirectional causal relationship running from Exchange Rate to infrastructure growth”. Keywords: Cointegration, External debt, Exchange rate, Granger causality, Infrastructure growth, Unit root, Vector Error Correction, Vector Autoregression.
MPhil. Finance
Keywords: Cointegration; Exchange Rate; External Debt; Infrastructure Growth; Vector Autoregression